The cytotoxicity effect of ant-444 in human chronic myeloid leukaemia cells (K 562) - Khalid, Nor Bahijah; Abdul Ghani, Radiah (2013)
The era of chemotherapy began in the 1940s with the first uses of nitrogen mustards and antifolate drugs. To develop drugs for specific cancer-related targets, researchers from multiple disciplines have joined together in the search for more effective cancer drugs (Chabner & Roberts, 2005). Unfortunately, these chemotherapy drugs are not specific and do not differentiate between killing tumor cells and normal cells, leading to the many common side effects associated with cancer chemotherapy (MacDonald, 2009). Therefore, with the intention of increasing the specificity of anti-cancer drugs targeting as well as decreasing the side effect of the drugs, many studies on polyamine concentration were done since years ago.This project was carried out as a preliminary study with aim to investigate the cytotoxicity effect of a polyamine anthracene conjugate, namely Ant-444 in a human chronic leukemic cell line which is K562. We assessed the cytotoxicity effect of the Ant-444 on the cells by using (3-(4,5)-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) colorimetric (MTT) assay and trypan blue dye exclusion method.The result revealed that the drug has the ability to inhibit the growth of cancer cells by showing an IC50 value of 2.4 μM and growth curve results obtained show a significant inhibition of K562 cell growth after been exposed 48 hours to the Ant-444 (96 hour in culture)(P<0.05 at 96 hour and P< 0.001at 120 and 144 hour). In conclusion, the findings obtained confirmed that the drug; Ant-444, has cytotoxic effect against K562 cell line. This basic study will help in providing scientific justification for the use of this polyamine anthracene conjugate in treating cancer.